Serum lipids, lipoproteins and apolipoproteins in pregnant non-diabetic patients. Issue 8 (August 1994) - Mazurkiewicz, J C; Watts, G F; Warburton, F G; Slavin, B M; Lowy, C; Koukkou, E
Abstract : AIMS–To investigate the effect of pregnancy on serum concentrations of lipids, lipoproteins, and apolipoproteins. METHODS–Fasting serum concentrations of total cholesterol, triglyceride, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL), apolipoproteins AI, AII, and B, and lipoprotein (a) were measured in 178 women with normal glucose tolerance in the second and third trimesters of pregnancy and in a control group of 58 non-pregnant women of similar age. Data were analysed using the unpaired t test and by one-way analysis of variance. RESULTS–The pregnant women had significantly higher concentrations of total cholesterol, triglyceride, LDL cholesterol, HDL cholesterol, and apolipoproteins AI and B (p < 0.001) and apolipoprotein AII (p = 0.003) than the control women. The ratio of apolipoprotein B:apolipoprotein AI was significantly higher in the pregnant women than in the controls (p < 0.001), but the total cholesterol:HDL cholesterol ratio was not significantly different. No significant difference was found in the concentration of lipoprotein (a). CONCLUSIONS–Hyperlipidaemia is common in the second half of pregnancy. This may be a purely physiological response to pregnancy or it may be indicative of pathology in some women. These results warrant a follow up study to investigate whether the hyperlipidaemic response to pregnancy is variable and if so, whether it can predict future hyperlipidaemia in a manner analogous to that of impaired glucose tolerance during pregnancy, predicting non-insulin dependent diabetes in later life.